Chronic non-freezing cold injury results in neuropathic pain due to a sensory neuropathy - Vale, T; Symmonds, M; Polydefkis, M; Byrnes, K; Rice, A; Themistocleous, A; Bennett, D (Oxford University Press, 2017)
Non-freezing cold injury (NFCI) develops after sustained exposure to cold temperatures, resulting in tissue cooling but not freezing. This can result in persistent sensory disturbance of the hands and feet including numbness, paraesthesia and chronic pain. Both vascular and neurological aetiologies of this pain have been suggested but remain unproven. We prospectively approached patients referred for clinical assessment of chronic pain following non-freezing cold injury between 12 February 2014 and 30 November 2016. Of 47 patients approached 42 consented to undergo detailed neurological evaluations including: questionnaires to detail pain location and characteristics, structured neurological examination, quantitative sensory testing, nerve conduction studies and skin biopsy for intra-epidermal nerve fibre assessment. Of the 42 study participants, all had experienced NFCI whilst serving in the United Kingdom armed services and the majority were of African descent (76.2%) and male (95.2%). Many participants reported multiple exposures to cold. The median time between initial injury and referral was 3.72 years. Pain was principally localised to the hands and the feet, neuropathic in nature and in all study participants associated with cold hypersensitivity. Clinical examination and quantitative sensory testing were consistent with a sensory neuropathy. In all cases large fibre nerve conduction studies were normal. The intra-epidermal nerve fibre density was markedly reduced with 90.5% of participants having a count at or below the 0.05 centile of published normative controls. Using the Neuropathic Pain Special Interest Group (NeuPSIG) of the International Association for the Study of Pain (IASP) grading for neuropathic pain 100% had probable and 95.2% definite neuropathic pain. Chronic non-freezing cold injury is a disabling neuropathic pain disorder due to a sensory neuropathy. Why some individuals develop an acute painful sensory neuropathy on sustained cold exposure is not yet known but individuals of African descent appear vulnerable. Screening tools, such as the DN4 questionnaire, and treatment algorithms for neuropathic pain should now be used in the management of these patients.